Pollution Tax Under Imperfect Competition and Air Transport in a Domestic Economy - Kareem, Salami Dada; Sunkanmi, Odubunmi Ayoola; Kehinde, Atoyebi; Samad, Lawal A (International Journal of Business, Economics and Management, 2017)
This paper empirically demonstrates the possibility of setting up an optimal pollution tax under imperfect markets and international trade in a domestic economy. The model illustrates a situation of partial equilibrium characterized by imperfect competition among domestic producers, where the domestic good is used as an alternative for an imported polluting commodity. In this paper, we bring in the possibility that the domestic firms can introduce innovative ideas through investment in R&D. The result shows that the optimal pollution tax under domestic economic distortions is a function of a ‘domestic production effect’ and a ‘pollution effect’. The paper concludes that when the firms execute R&D expenditures, the optimal policy adds an ‘innovative effect’, which captures the change in welfare coming from a reduction in total costs and this lead our results to a win-win situation.